ANALISIS PENGARUH KESADARAN MEREK, PERSEPSI HARGA, DESAIN WEB, TERHADAP MINAT BELI PADA ZENIUS EDUCATION (Studi pada Perilaku Generasi Z Khusus Siswa Dikabupaten Demak) - Rahman, Aulia; Astuti, Sri Rahayu Tri (Faculty of Economics and Business Diponegoro University, 2019)
Generation Z is known as the internet generation. Generation Z is a teriminologi which has become a hot topic in the modern era. The number of conversations that can be discussed from generation Z. therefore this study aims to determine the effect of brand awareness, perceived price, web design on buying interest in Zenius.net. Zenius.net is one of the digital learning media.The number of samples in this study were 100 respondents. The respondent is a Zenius.net user or consumer candidate in Demak Regency. This research was conducted in various schools in Demak Regency. The method used in collecting data through questionnaires and sampling methods in this study was taken using incidental sampling and purposive sampling. The analytical method used is a quantitative method that includes validity and reliability tests, classic assumption tests, multiple regression analysis, t test, F test, and Determination coefficient throughaSPSSaanalysismtools.The results showed that brand awareness, perceived price and web design influence buying interest. or Can be concluded that the three variables have an influence on buying interest and are positive or in the direction of buying interest. The findings of this study indicate that web design variables are the most influential variables on buying interest.